Elihu jako mędrzec w historii egzegezy Księgi Hioba na przykładzie anonimowego "Commentarii in Job". - Jóźwiak, Magdalena (Vox Patrum, 2019)
Elihu is the first amongst the ancient commentators in the history of exegesis of the Book of Job. Currently, he is becoming more and more popular as a subject of research on the Book of Job. Regarding the Elihu’s appearance, most of exegetes take the view that his speech must have been included in the Book of Job at a later time, because Elihu had been mentioned neither in the prologue, nor in the epilogue of the original text. Also, the language of his articulation differs from the language of Job’s three other friends. Additionally, his speeches don’t show the structure of a dialogue, and the main subject of Elihu’s speech differs from arguments put forward by his predecessors in discussion. In this present article I analysed the person of Elihu on the example of anonymous Commentarii in Job. This subject has been presented in three scenes. Firstly, I summarised Commentarii in Job that was also a subject of my Ph.D. dissertation. Secondly, I drew the image of Elihu, as it emerges from the analysed commentary. The final and the most important section depicts Elihu’s relation to God, to Job and Job’s three friends, based on Commentarii in Job. Fragments of Commentarii in Job are the author’s own translations.